Lactic acid bacteria secrete metabolites retaining anti-inflammatory properties after intestinal transport. Issue 6 (11th May 2004) - Ménard, S; Candalh, C; Bambou, J C; Terpend, K; Cerf-Bensussan, N; Heyman, M
Abstract : Background: Probiotic bacteria have a beneficial effect on intestinal inflammation. In this study, we have examined the effect of lactic acid and commensal Gram positive (+) bacteria conditioned media (CM) on tumour necrosis factor α (TNF-α) release and the mechanisms involved. Methods: Lipopolysaccharide (LPS) induced TNF-α secretion by peripheral blood mononuclear cells or the THP-1 cell line was monitored in the presence or absence of bacteria CM obtained from two probiotic strains, Bifidobacterium breve ( Bb ) and Streptococcus thermophilus ( St ), and three commensal bacterial strains ( Bifidobacterium bifidum, Ruminococcus gnavus, and unidentified Streptococcus ). Bb and St bacteria CM were allowed to cross filter grown intestinal epithelial cell monolayers (HT29-19A) to assess intestinal transport of active bacterial products. These products were characterised and their effect on LPS binding to THP-1 cells and nuclear factor κB (NFκB) activation assessed. Results: Dose dependent inhibition of LPS induced TNF-α secretion was noted for both probiotic bacteria CM (64% and 71% inhibition for Bb and St, respectively) and to a lesser extent commensal bacteria CM (21–32% inhibition). Active products from Bb and St were resistant to digestive enzymes and had a molecular mass <3000 Da. Their inhibitory effect was preserved after transepithelial transport across intestinal cell monolayers, mainly in inflammatory conditions. LPS-FITC binding to THP-1 cells and NFκB activation were significantly inhibited by Bb and St CM. Conclusion: B breve and S thermophilus release metabolites exerting an anti-TNF-α effect capable of crossing the intestinal barrier. Commensal bacteria also display a TNF-α inhibitory capacity but to a lesser extent. These results underline the beneficial effect of commensal bacteria in intestinal homeostasis and may explain the role of some probiotic bacteria in alleviating digestive inflammation.